(untitled) (Ustozlar uchun, 2024)
ABSTRACT. The article presents information on the clinical course of infectious mononucleosis in 142 patients aged 1 to 14 years living in the Samarkand region. It was found that at the current stage, the disease retains all the features of its clinical course. If the diagnosis of infectious mononucleosis is made in time and accurately, the effectiveness of treatment in infected patients is shown by reducing the duration of fever, the severity of the proliferative syndrome in the lymph nodes, and the faster cessation of the cytolysis process.